Management of alcohol use disorder in patients with cirrhosis in the setting of liver transplantation - Arab, Juan Pablo; Izzy, Manhal; Leggio, Lorenzo; Bataller, Ramon; Shah, Vijay H. (Nature reviews. Gastroenterology & hepatology, 2022)
The prevalence of alcohol use disorder (AUD) has been steadily increasing over the past decade. In parallel, alcohol-associated liver disease (ALD) has been increasing at an alarming rate, especially among young patients. Data suggest that most patients with ALD do not receive AUD therapy. Although liver transplantation is the only curative therapy for end-stage ALD, transplant candidacy is often a matter of debate given concerns about patients being under-treated for AUD and fears of post-transplantation relapse affecting the allograft. In this Review, we discuss diagnosis, predictors and effects of relapse, behavioural therapies and pharmacotherapies, and we also propose an integrative, multidisciplinary and multimodality approach for treating AUD in patients with cirrhosis, especially in the setting of liver transplantation. Notably, this approach takes into account the utility of AUD pharmacotherapy in patients on immunosuppressive medications and those with renal impairment after liver transplantation. We also propose a comprehensive and objective definition of relapse utilizing contemporary biomarkers to guide future clinical trials. Future research using the proposed approach and definition is warranted with the goal of optimizing AUD treatment in patients with cirrhosis, the transplant selection process and post-transplantation care of patients with AUD. In this Review, Arab and colleagues discuss management of alcohol use disorder in patients with alcohol-associated liver disease, particularly in the setting of liver transplantation. An integrative, multidisciplinary approach is proposed. Key points The prevalence of alcohol use disorder (AUD) and alcohol-associated liver disease has increased over the past few decades globally. Definitions of relapse after liver transplantation vary widely. Currently, our understanding of the predictors and effects of relapse after liver transplantation is growing and together with a multidisciplinary approach might improve patient outcomes. The use of pharmacotherapies for AUD is feasible in patients with cirrhosis after tailoring the regimen to account for comorbid illnesses such as renal dysfunction. Relapse-prevention medications do not have notable interactions with immunosuppressants commonly used after liver transplantation. Combining medications and behavioural treatments with medical care at the transplant centre might maximize relapse prevention potential.